Poly(acrylonitrile) ultrafiltration membranes. I. polymer-salt-solvent interactions - Phadke, M. A.; Musale, D. A.; Kulkarni, Sudhir S.; Karode, Sandeep K. (Journal of Polymer Science Part B: Polymer Physics, 2005)
Fourier transform infrared spectroscopy was used to study the interactions among LiCl, ZnCl2, and AlCl3 with NN-dimethylformamide (DMF) and poly (acrylonitrile) (PAN). It was observed that all three salts complex with DMF as well as PAN. The strength of the cation interaction with the > C=O oxygen of DMF was found to be higher than that with the -CN group of PAN. The > C=O stretching frequency of DMF with ZnCl2 was red shifted, indicating stronger complex formation compared with other two cations. With the addition of salt, the salt-DMF pseudo solvent was found to become a 0 solvent for PAN compared with neat DMF. This change in PAN solvation power was primarily the result of DMF-salt complexation. As a result of the complexation, Mark-Houwink constant a, was found to reduce from 0.75 (for pure DMF) to similar to 0.6 for DMF-salt solvents, indicating decreased PAN chain expansion. Comparison of intrinsic viscosity [n] values indicated that addition of salts to PAN-DMF solutions resulted in: (i) decrease in the DMF solvation. power, which causes less expanded polymer coils, and (ii) increased interpolymer chain entanglements via salt-promoted chain association. (c) 2005 Wiley Periodicals, Inc.
Keywords: activation energy viscosity; Additives; FT-IR; Poly(acrylonitrile); solution properties

Poly(acrylonitrile) ultrafiltration membranes. II. membrane morphology and permeation characteristics - Phadke, M. A.; Kulkarni, Sudhir S.; Karode, Sandeep K.; Musale, D. A. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The rheology and phase-boundary characteristics of various solutions comprising three polyacrylonitrile (PAN) grades dissolved in solutions of N,N-dimethylformamide + salt (LiCl, ZnCl2, or AICl(3)) additives were correlated with the resulting membrane morphology as determined by microscopy and permeability measurements. The phase separation characteristics of the dope solution were not markedly affected by the PAN molecular weight (MW); however, they were affected by the salt additive. For higher MW grades, the effect of salt addition can also be masked by the increased self-association tendency of the polymer chains. PAN-B and -C membranes were clearly less asymmetric in structure than the lower MW PAN-Abased membranes. This is attributed to the higher viscosity/lower diffusivity of the PAN-13 and -C solutions, which results in slower solvent-nonsolvent exchange during the phase inversion process. Two factors reduce the incidence of surface defects (increased bubble points): (a) higher solution viscosity dampens surface perturbations during phase inversion, and (b) phase inversion pathways resulting in more homogenous morphology lead to membranes with higher bubble points. (c) 2005 Wiley Periodicals, Inc.
Keywords: bubble point; membranes; Morphology; phase inversion; salts; viscosity